“It is time for the slaves to speak:” transatlantic abolitionism and African American activism in Britain 1835-1895 - Murray, Hannah-Rose (2018)
During their transatlantic journeys to Britain throughout the nineteenth century, African Americans engaged in what I term “adaptive resistance,” a multi-faceted interventionist strategy by which they challenged white supremacy and won support for abolition. Alongside my recovery of this mode of self-presentation in sources I have excavated from Victorian newspapers, I use an interdisciplinary methodology that draws on literary studies, cultural history, memory studies, African American studies and the visual culture of antislavery iconography to (re)discover black performative strategies on the Victorian stage from the late 1830s to the mid 1890s. Performance was only one strand in the black activist arsenal, however. The successful employment of adaptive resistance relied on a triad of performance, abolitionist networks and exploitation of print culture. For the first time, I have identified and unified these themes as central to black abolitionist transatlantic visits, and conclude that if an individual ensured an even balance between all three, it was likely their sojourn was successful. This changes our previous knowledge of black abolitionist missions, as we can use this analysis to explain why some activist visits were more successful than others.